Analysis and design of precast cast-in situ concrete composite - Ercia Emanuela da Costa; Tony Hartono Bagio (NAROTAMA UNIVERSITY, Indonesia, 2022)
The quay is a building structure made at sea to connect the land and harbor parts that function as a place for docking or mooring ships that will carry out loading and unloading activities of loading and unloading passengers. The wharf at the Tibar port is operated for loading/unloading general cargo containers. The dimensions of the floor plate for the wharf are 75cm, T4 transverse beams 6,900 x 1,500 x 1,500 m, longitudinal beams 5,400 x 1,750 x 1,500 m, pile cap 1.69 m² and pile foundation length The pile for the diameter of 1.5 m is 80 m, the Pile of 1.8 m is 81 m. The wharf has a length of 630 m, a width of 62 m and a depth of 16 m and the structure type of this pier is reinforced concrete and steel piles.